Design and Measurement of a Frequency Converter with SPWM Modulation of Output Voltage for a Two-Phase Induction Motor - Kanuch, Jan; Girovsky, Peter; Zilkova, Jaroslava; Pastor, Marek (Elektronika ir Elektrotechnika, 2023)
This paper deals with the design, implementation, and measurements of a frequency converter with bipolar sinusoidal pulse width modulation (SPWM) of output voltage for two-phase induction motors. The paper is dedicated to an analysis of the operation of a two-phase frequency converter and its implementation. The inverter has a single-phase H-bridge topology with split DC link and bipolar switching to minimise the number of components. Insulated gate bipolar transistors (IGBTs) are used in the realisation of the inverter power section. The inverter is controlled using a digital signal processor (DSP) TMS320F28335. Measurements with a 0.12 kW two-phase induction motor were performed to verify the correct operation of the inverter. The influence of the switching frequency on the motor current ripple is measured for frequencies of the first harmonic up to 100 Hz.